The Effect Of The Adapted Sports Program To Adjust The Glycated Hemoglobin In Women With Diabetes Type 2 - Ghouissem, Abdelhamid; Cheriat, Abdelkader Hakim (sports creativity, 2025)
The objective of the study was to determine the effect of the adapted sports program to adjust the glycated hemoglobin in women with diabetes. The researchers adopted the empirical research by preparing a sports program adapted to the needs of this target group in order to measure the glycated hemoglobin after application of the program. The sample of the study was 18 women who were chosen by the intentional method and were divided into two groups. The first was a empirical and the second was a reference who had the tribal measurement tests. Then the adapted sports program was implemented into the empirical groupe divided in 36 sessions. The same ex-post tests were repeated into the tows groups. The researcher adopted the appropriate statistical tools for processing the data through the SPSS